KERAMIK SITUS SO LANGGODU, DOMPU: INDIKASI PERMUKIMAN MASA LALU - A.A. Gde Bagus (Forum Arkeologi, 2014)
The landform of So Langgodu Site is valley, surrounded by hills, rich in water sources so that the land is fertile. Settlement has existed since prehistoric era until the next period. The finding of ceramics in So Langgodu is important because it could reveal the social, cultural and economic life of the past. This study aims to reveal the function and role of the ceramics related to the settlement and trade. The methods used in this research are literature study, observation, and interviews. The data were analyzed using descriptive-qualitative approach. The ceramic fragments found in this research consists of plate, bowl, tube, and jar. All of the ceramic fragments originated from China. The presence of ceramics in So Langgodu is an indication of activity in past settlement and could not be separated from trading activity, obtained by exchanging or purchasing from foreign traders.Bentukan lahan Situs So Langgodu berupa lembah yang dikelilingi perbukitan dan memiliki sumber air melimpah sehingga tanahnya subur dan dimanfaatkan sebagai permukiman sejak masa prasejarah sampai masa berikutnya. Temuan keramik di Situs So Langgodu penting karena dapat mengungkap kehidupan sosial budaya dan ekonomi masa lalu. Tujuannya untuk mengungkap fungsi dan peran temuan keramik terkait permukiman dan perdagangan. Metode yang digunakan adalah kepustakaan, observasi, wawancara. Data dianalisis secara deskriptifkualitatif. Keramik yang ditemukan berupa pecahan piring, mangkuk, cepuk, dan buli-buli, serta temuan arkeologi lain. Semua temuan keramik berasal dari Cina. Kehadiran keramik di Situs So Langgodu merupakan sisa aktivitas permukiman dan terkait dengan perdagangan melalui pertukaran atau pembelian dengan pedagang asing.